2017
DOI: 10.1002/zoo.21388
|View full text |Cite
|
Sign up to set email alerts
|

Keeping and breeding the rescued Sunda pangolins (Manis javanica) in captivity

Abstract: The Sunda pangolin (Manis javanica Desmarest, 1822) is a Critically Endangered species. Given that this species lacks effective policies for in situ conservation and prevention of poaching in the wild, ex situ conservation and a captive breeding program are urgently needed to save this species from extinction. However, techniques for the maintenance and captive breeding of pangolins have not been well developed. In June 2010, we established the Pangolin Research Base for Artificial Rescue and Conservation Bree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…However, there was no obvious estrus behavior found in this study. In addition, 26 Sunda pangolins have been bred in captivity (Zhang et al, ), no obvious estrus behavior has been observed among female pangolins at PRB‐SCNU. We suggest two possibilities: either there are some minimal differences between estrus and non‐estrus behavior and further quantitative analysis is needed to distinguish, or the artificial habitat and lack of environmental enrichment may limit the expression of estrus behavior in captive Sunda pangolins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there was no obvious estrus behavior found in this study. In addition, 26 Sunda pangolins have been bred in captivity (Zhang et al, ), no obvious estrus behavior has been observed among female pangolins at PRB‐SCNU. We suggest two possibilities: either there are some minimal differences between estrus and non‐estrus behavior and further quantitative analysis is needed to distinguish, or the artificial habitat and lack of environmental enrichment may limit the expression of estrus behavior in captive Sunda pangolins.…”
Section: Discussionmentioning
confidence: 99%
“…The Sunda pangolin ( Manis javanica ) is one of eight extant pangolin species (Gaubert & Antunes, ). It is widely distributed throughout Southeast Asia including Singapore, Malaysia, Vietnam, Lao PDR, Thailand, Indonesia, and China (Challender et al, ; Zhang et al, ). An increase in the trade of pangolin meat, scales, and live individuals has led to the capture of an estimated one million pangolins over the past decade; the pangolin has become one of the most frequently illegally traded mammals in the world (IUCN, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reproductive behavior [12] and the success of captive breeding in the Malayan pangolin have been reported [13]. The reproductive biology in male Malayan pangolins has also been explored recently [14,15].…”
Section: Introductionmentioning
confidence: 99%